A new type of wind-resistance cable net for narrow suspension bridges and wind-resistance cable element for its calculation. (October 2021) - Qi, Dongchun; Chen, Xinghua; Zhu, Yiwen; Zhang, Qi
Abstract: In this paper, a new-style cable net structure consisting of a wind-resistance main cable, wind-resistance secondary cable and pulleys is proposed to improve the wind-resistance stability of narrow suspension bridges. In the improved structure, the wind-resistance secondary cable which slides on pulleys to achieve uniform distribution of cable force. However, the calculation for this structure is very difficult due to the sliding cable, which means the unstressed length of the cable between the pulleys is not fixed. To this end, a multi-node wind cable element considering the cable sliding on nodes is proposed for the wind-resistance secondary cable. Additionally, an analytical model of the wind cable element is established according to the structural features. The unstressed state method, virtual work principle and influence matrix method are all used to deduce and verify the tangent stiffness matrix of the element. As a result, the exact nodal forces can be calculated according to the static equilibrium conditions and the proposed element implemented for the nonlinear finite element analysis of the suspension bridge. Numerical and bridge examples are used to demonstrate that the new element can successfully simulate the sliding of the cable on the pulleys, and be applied to the nonlinear finite element calculation like any normal element. By means of this method, a wind-resistance secondary cable with any cable section connected by pulleys to the wind-resistance main cable and stiffening girder, can be accurately simulated with only one wind cable element. Hence, the calculation problem of the wind-resistance cable is resolved and overall calculation accuracy and efficiency are improved.